DESIGN AND USABILITY EVALUATION OF A MOBILE TOURISM APPLICATION BASED ON USER-CENTERED DESIGN APPROACH - Ricco Herdiyan Saputra; Mezan El-Khaeri Kesuma (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2026)
Mobile tourism applications play a crucial role in supporting travelers’ information search and trip planning; however, many existing systems still suffer from usability limitations that affect user satisfaction and continued use. This study aims to design and evaluate a mobile tourism application prototype using a user-centered design (UCD) framework combined with the System Usability Scale (SUS) for quantitative validation. The development process involved user needs identification, iterative prototyping, and structured usability testing with 20 participants aged 18–35 years. The evaluation results yielded a mean SUS score of 82.5 (SD = 6.8), categorizing the prototype within the “Excellent” usability level. All participants successfully completed the assigned tasks, indicating strong learnability and interaction clarity. These findings demonstrate that integrating UCD with standardized usability benchmarking provides measurable evidence for improving mobile tourism interface quality and supports early-stage validation prior to full-scale implementation.